LA PENALIZACIÓN DE LOS MENORES ADULTOS EN EL DELITO DE VIOLACIÓN - Maza Cunanchi, Karla Elizabeth (2015)
This thesis entitled "The Criminalization of Adult Children of Rape Crime" discusses criminal responsibility should be attributed to minors who commit adult crimes of rape, for violating the right to sexual integrity and privacy of the people who are victims younger adults who taking advantage of his insanity, and the imposition of educational measures which do not serve the coercive nature of rehabilitation for juvenile offenders, they continue to violate the sexual integrity of other people also start their life of crime by not immediately intervene state, society and family, they will become dangerous criminals to the community; therefore it is necessary to be penalized, ie, should be tried with imprisonment established in Art. 171 of the crime of rape under the Code of Integral Criminal, as adults, having considered that the Constitution of the Republic of Ecuador allows the optional right to vote because at that age can already discern between good and actions that harm the rights of others and other domestic laws take into account their decisions as minors and adults be able to decide; this should be considered because its development from biologically and psychologically have a great understanding of what they want to do and their legal and social consequences. The theoretical and field work of this thesis has allowed me to get criteria, with clear and precise grounds of well known literature, which contributed to the verification of targets, and testing of the hypothesis, allowing support 5 reforms to the Organic Law Children and Adolescents of Ecuador, with regard to responsibility adult child. The content of this thesis is the result of an arduous legal research of author in the scientific, legal, social and methodological level, which deals with theories and knowledge gained through scientific and statistical techniques and methods.